A Better Engineering Design: Low Cost Assistance Kit for Manual Wheelchair Users with Enhanced Obstacle Detection - Dryvendra, Dryvendra; Ramalingam, Mritha; Chinnavan, Elanchezhian; Puviarasi, Puviarasi (ITB Journal Publisher, LPPM ITB, 2015)
This paper proposes a better engineering design of an assistance kit for manual wheelchair users. The design is aimedÂ to enhance the detection of obstacles in the travelling path of the wheelchairÂ user at low cost. This is facilitated by microcontroller and sensor technologies. The proposed design provides the intended user with obstacle detection, light detection, a light emitting diode (LED) emergency light system, and an emergency alarm system. The microcontroller is the main controller that receives input from the sensors and produces output to the light crystal display (LCD) screen, the LED emergency light system, and the emergency alarm system. An ultrasonic sensor is used to detect the presence of obstacles directly behind the wheelchair. If any obstacle exists behind the wheelchair within a set range, the system will alert the wheelchair user through different alarm sounds. In the case of absence of light, the LED emergency light system is activated and turns on a light source, which is attached to the wheelchair to provide a bright and clear path for the user. The distance between the obstacle and the wheelchair, and the status of the LED emergency light system are displayed on the LCD screen.